Is an Alternative Globalization Possible? - Evans, Peter (Politics & Society, 2008)
Building on Polanyi's concept of the “double-movement” through which society defends itself against domination by the self-regulating market, this article sets out some key organizational and ideological hurdles that the contemporary “movement of movements” must surmount to challenge the hegemony of neo-liberal globalization. After outlining neo-liberalism's failures, it makes an argument for the possibility of “counter-hegemonic globalization,” defined as a globally organized project of transformation aimed at replacing the dominant (hegemonic) global regime with one that maximizes democratic political control and makes the equitable development of human capabilities and environmental stewardship its priorities.
Sociology
Keywords: double movement; globalization; neoliberalism; social movements; transnational networks